2015
DOI: 10.1007/s00432-015-2025-z
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant endocrine therapy in pre- versus postmenopausal patients with steroid hormone receptor-positive breast cancer: results from a large population-based cohort of a cancer registry

Abstract: Purpose Adjuvant endocrine therapy (ET) is indicated in patients with steroid hormone receptor (HR)-positive breast cancer. The aim of this study was to evaluate the quality of HR determination and adjuvant endocrine treatment of breast cancer patients in a large cohort of more than 7000 women by analyzing data from a population-based regional cancer registry.MethodsData from the Clinical Cancer Registry Regensburg (Bavaria, Germany) were analyzed. Female patients with primary, nonmetastatic invasive breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…Immuno-histochemical determination of 4-IHC was performed consistent with defined standards as described in detail in previous studies of our group [ 10 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Immuno-histochemical determination of 4-IHC was performed consistent with defined standards as described in detail in previous studies of our group [ 10 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Historically, concerns about the completeness and accuracy of registry data led to caution when using these data to assess care quality; however, more recent studies have demonstrated improvements in registry data, [19][20][21][22][23] and investigators are now using them to measure quality. 24,25 Still, we excluded measures that could not be ascertained from registry data (eg, use of tumor markers or imaging studies). A concordance value was derived for each measure using the overall percentage method, 26 in which concordance equals the number of patients who received recommended care divided by the number eligible for each measure.…”
Section: Methodsmentioning
confidence: 99%
“…In Bavaria, the law on the Bavarian Epidemiologic Cancer Registry (Gesetz über das bevölkerungsbezogene Krebsregister Bayern-BayKRG) allows the continuous and uniform data acquisition and processing of cancer incidences by means of an epidemiologic cancer registry [9]. The purpose of this law is to regulate cancer control and to improve data quality of cancer epidemiology.…”
Section: Cancer Registration In Bavariamentioning
confidence: 99%
“…Each patient has the right to object data storage at any time. On the basis of this law, retrospective analyses of anonymous data require no additional ethics statement [9].…”
Section: Cancer Registration In Bavariamentioning
confidence: 99%